The simulated dynamical photovoltaic array systems - Guangyu Liu; Sing Kiong Nguang; Yuan Ren (2010 International Conference on Information and Automation, 2010)
Temporal performance of a generic stand-alone photovoltaic (PV) array system was simulated numerically under the influence of the environmental variables: irradiation and temperature and a variable external power demand. The temporally and spatially distributed irradiation and temperature were integrated to the solution of the nonlinear PV array model. The PV power output that was regulated by DC-DC converter with or without MPPT functioned together with a battery bank subsystem to meet the external power demand. Results showed that temporal performance of the simulated system can be quantified and described explicitly at the presence of those external time-varying variables. It suggests that the simulated systems subject to the time-varying conditions can be used to assist the design, reduce the cost of analysis and test, and investigate the performance of various applications of PV array systems.